Strategic Choice of Technology Transfer in Indonesia - Syafrizal Maludin; Rizal Syarief; Amzul Rifin; Nurul Taufiqu Rochman (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Research shows technology development is one key element of economic growth. The race in innovation technology leads the government to issue policies in order to enhance competitiveness based on innovation technology. This commitment is mostly followed by allocating some amount of budget in science and technology development. On the other side, it should be comprehended that innovation creates its own arteries which encourage the government to create an appropriate strategic choice which meets the expectation based on the unique competence of a nation. This article measures the strategic choice for policy maker in establishing an appropriate technology transfer system based on the opinion of actors that involve in technology transfer utilizing analytical hierarchy process (AHP) that analyzes the individual variables in three hierarchies. The variables were derived from the first discussion with experts as the higher level of decision maker. Additionally, research problems were based on the first process of discussion of AHP with experts enriched by literature study. The choices of strategy in this research include developing technology & business incubator at 0.50414, establishing science attaché at 0.24344, strengthening existing public research institution at 0.16648 and increasing gross expenditure on research and development at 0.08594.Keywords: AHP, policy maker, technology transfer, strategic choicesAbstrak: Riset menunjukan peran perkembangan teknologi sebagai salah satu elemen penting dalam pertumbuhan ekonomi. Kompetisi dalam arena inovasi teknologi berpengaruh pada pemerintah untuk mengeluarkan kebijakan dalam penguatan daya saing bangsa berbasis inovasi teknologi. Komitmen ini seringkali diikuti dengan alokasi anggaran untuk kegiatan riset dan teknologi. Namun, penguatan ini harus diikuti dengan pemahaman bahwa inovasi menciptakan alur prosesnya sehingga pemerintah diharapkan mampu menciptakan pilihan strategi yang searah dengan tujuan yang berakar dari nilai lokal. Tulisan ini mengukur pilihan strategi yang dapat digunakan oleh pembuat kebijakan dalam menciptakan alih teknologi yang didasarkan pada visi pakar pada bidang alih teknologi dengan menggunakan pendekatan analytical hierarchy process (AHP) yang terbagi dalam tiga struktur hirarki. Variabel yang digunakan diturunkan dari interview pertama dengan pakar dan pengambil keputusan. Masalah riset pada kajian ini juga diturunkan dari interview dengan pakar yang diperkaya dengan penelaahan literatur. Pilihan strategi pada kajian ini adalah pengembangan inkubator dan taman sains dan teknologi 0,50414, pembukaan attaché iptek 0,24344, penguatan litbang 0,16648 dan peningkatan anggaran riset 0,08594. Kata kunci: AHP, alih teknologi, pembuat kebijakan, pilihan strategi